Comment on Civil Law and Common Law: Two Different Paths Leading to the Same Goal - Nottage, Luke (Victoria University of Wellington Law Review, 2001)
This article discusses civil and common law in the context of Caslav Pejovic’s article of the same name. Pejovic noticed a trend where common law was increasingly hemmed in by legislation while law jurisdictions were increasingly reliant on precedent set by the courts. Pejovic therefore called for the unification of private law globally. Nottage then explores how different academics approached a potential convergence/divergence dichotomy within civil and common law. The article suggests that a "middle ground" dimension between convergence and divergence is a possible development. The author ultimately advocates for the middle ground dimension as it provides socio-economic context for laws, as well as promoting exegesis in statutory and case analysis. The author thus concludes that convergence and divergence are both valuable.